2020
DOI: 10.3389/fimmu.2020.00691
|View full text |Cite
|
Sign up to set email alerts
|

ILC2 Lung-Homing in Cystic Fibrosis Patients: Functional Involvement of CCR6 and Impact on Respiratory Failure

Abstract: Cystic fibrosis patients suffer from a progressive, often fatal lung disease, which is based on a complex interplay between chronic infections, locally accumulating immune cells and pulmonary tissue remodeling. Although group-2 innate lymphoid cells (ILC2s) act as crucial initiators of lung inflammation, our understanding of their involvement in the pathogenesis of cystic fibrosis remains incomplete. Here we report a marked decrease of circulating CCR6 + ILC2s in the blood of cystic fibrosis patients, which si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 93 publications
(114 reference statements)
2
21
0
Order By: Relevance
“…We have previously reported increased ILC2 frequencies in the intestine of patients with inflammatory bowel disease 17 and in the lungs of patients with asthma, 49 likely due to their influx from the circulation. In line with this, it is possible that the lower ILC frequencies observed in severe as compared with moderate COVID‐19 patients could indicate potential trafficking of ILC2 to inflamed infection sites as previously described in asthma 49 and cystic fibrosis 50 . In striking resemblance with the latter study, we observed the lowest frequencies of ILC2 in patients with the highest serum levels of CCL20, and reduced frequencies of CCR6 + ILC2 in COVID‐19 patients.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…We have previously reported increased ILC2 frequencies in the intestine of patients with inflammatory bowel disease 17 and in the lungs of patients with asthma, 49 likely due to their influx from the circulation. In line with this, it is possible that the lower ILC frequencies observed in severe as compared with moderate COVID‐19 patients could indicate potential trafficking of ILC2 to inflamed infection sites as previously described in asthma 49 and cystic fibrosis 50 . In striking resemblance with the latter study, we observed the lowest frequencies of ILC2 in patients with the highest serum levels of CCL20, and reduced frequencies of CCR6 + ILC2 in COVID‐19 patients.…”
Section: Discussionsupporting
confidence: 90%
“…In line with this, it is possible that the lower ILC frequencies observed in severe as compared with moderate COVID-19 patients could indicate potential trafficking of ILC2 to inflamed infection sites as previously described in asthma 49 and cystic fibrosis. 50 In striking resemblance with the latter study, we observed the lowest frequencies of ILC2 in patients with the highest serum levels of CCL20, and reduced frequencies of CCR6 + ILC2 in COVID-19 patients. Hence, our data point towards a role for CCL20mediated recruitment of CCR6 + ILC2 to the lung of COVID-19 patients, where they could contribute to fibrosis.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Chemokine receptors and integrins and their binding partners shape the homing patterns of cells and ostensibly, EXO in the body (48). Of particular note are the chemotactic and adhesion factors identified in reg DCs EXO (Figure 6), including CCR6, CCR7, CXCR2, Integrin alpha-M (CD11b), Integrin beta-1 (CD29), CD47, Integrin alpha-1 (CD49a), ICAM-1(CD54), integrin beta-2, integrin alpha-5, and integrin alpha-L (LFA1) (49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60). CCR7 (50) mediates blood-derived lymphocyte trafficking to bronchial associated lymphoid tissue while CXCR2 directs neutrophil recruitment to the lungs (51).…”
Section: Discussionmentioning
confidence: 99%